2001
DOI: 10.1074/jbc.m100747200
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Induces Programmed Cell Death in Human Vascular Endothelial Cells through Activation of the Unfolded Protein Response

Abstract: Severe hyperhomocysteinemia is associated with endothelial cell injury that may contribute to an increased incidence of thromboembolic disease. In this study, homocysteine induced programmed cell death in human umbilical vein endothelial cells as measured by TdTmediated dUTP nick end labeling assay, DNA ladder formation, induction of caspase 3-like activity, and cleavage of procaspase 3. Homocysteine-induced cell death was specific to homocysteine, was not mediated by oxidative stress, and was mimicked by indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(206 citation statements)
references
References 48 publications
11
190
1
4
Order By: Relevance
“…These effects in gene expression directly involve the UPR because homocysteine treatment has been shown to induce the activation of both PERK 80,81 and IRE-1. 23 Severe or prolonged ER stress elicited by homocysteine has been shown to activate several cellular functions involved in the development and progression of atherosclerosis, including dysregulation of lipid metabolism, apoptotic cell death, and inflammation. We as well as others have demonstrated recently that homocysteine-induced ER stress causes dysregulation of lipid biosynthesis in hepatocytes by activating the SREBPs, 56,82 which are ER-resident transcription factors responsible for the induction of genes in the cholesterol/triglyceride biosynthesis and uptake pathways.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects in gene expression directly involve the UPR because homocysteine treatment has been shown to induce the activation of both PERK 80,81 and IRE-1. 23 Severe or prolonged ER stress elicited by homocysteine has been shown to activate several cellular functions involved in the development and progression of atherosclerosis, including dysregulation of lipid metabolism, apoptotic cell death, and inflammation. We as well as others have demonstrated recently that homocysteine-induced ER stress causes dysregulation of lipid biosynthesis in hepatocytes by activating the SREBPs, 56,82 which are ER-resident transcription factors responsible for the induction of genes in the cholesterol/triglyceride biosynthesis and uptake pathways.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…23 Apoptotic cell death was dependent on IRE-1 signaling and was also induced by other ER stress agents, including tunicamycin and thapsigargin. Homocysteine-induced IRE-1 activation causes a rapid and sustained activation of JNK protein kinases, 84 a result consistent with the finding that activation of JNK by ER stress involves binding of IRE-1 to TRAF2.…”
Section: Hhcy Er Stress and Apoptotic Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance of protein folding under various physiological or pathological conditions, such as alteration of cellular redox, deprivation of glucose, aberration of Ca 2+ regulation, and viral infections, creates the ER stress [20] . Wei et al reported that exposure to Hcy of the rat embryonic heart-derived cell line H9c2 can increase the expression of ER stress response genes, such as glucose regulated protein 78 (GRP78), C/EBP homologous protein (CHOP), and cleaved caspase-12 [21] , suggesting that ER stress is involved in the mechanisms of Hcy-induced cellular dysfunction [8,[22][23][24][25] . Therefore, it is logical to speculate that inhibiting Hcy-induced ER stress may be a novel therapeutic strategy to prevent and ameliorate AD progression.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial pellet was suspended in phosphate-buffered saline (PBS), centrifuged at 2,300 g for 15 min and frozen at −80°C overnight. Extraction of proteins from the pellet was done using the B-PER Bacterial Protein Extraction Reagent (Pierce, Rockford, endoplasmic reticulum (ER) stress (Zhang et al 2001). Homocysteine-induced ER stress contributes to the development of atherosclerosis in apolipoprotein E-deficient mice (Zhou et al 2004) and a high level of plasma homocysteine is one of the risk factors for atherosclerosis (Lawrence et al 2003), ischemic cardiovascular diseases, cerebrovascular diseases, and thrombosis ).…”
Section: Recombinant Herp Proteinmentioning
confidence: 99%